The Effect of Shor's Strategy on The Achievement of Primary School Students (Journal of the College of Basic Education, 2024)
The current research aims to identify the effect of Shor's strategy on the achievement of primary school students.In light of the research objective, the researcher formulated the following null hypothesis: (There is no statistically significant difference at the level of significance (0.05) between the average grades of the experimental group students who will study mathematics according to the Shor strategy and the average grades of the control group students who will study the same subject according to the Shor strategy. According to the usual method in the achievement test. To achieve the goal of the research and its hypothesis, the researcher adopted an experimental design with partial control for the post-test of academic achievement for the two research groups. The researcher intentionally chose Al-Warka Primary School for Boys affiliated with the General Directorate of Education in Diyala/Mansouriya District.The researcher determined the subject that would be taught during the experiment period, which amounts to three chapters from the Mathematics Book, 4th Edition (2023 AD), (Second Semester, Third Semester, and Fourth Semester) and formulated behavioral objectives for the topics to be taught. There were (131) behavioral objectives according to Bloom’s classification of cognitive objectives. The researcher prepared the research tool, which consisted of an achievement test in mathematics of the multiple choice type, consisting of (25) items. The researcher used the statistical package (spss), and after analyzing the results statistically, he concluded that the students of the experimental group who studied mathematics with the (Shor) strategy excelled over Control group students who studied mathematics in the usual way in the achievement test. In light of the research results, the researcher reached a number of conclusions, recommendations and proposals that were mentioned in Chapter Four.